Conversion in laparoscopic gastric cancer surgery a highlight on the abdominal access - Zengin, Akile; Bag, Yusuf Murat; Aydin, Mehmet Can; Kayaalp, Cuneyt (Annals of Medical Research, 2021)
Aim: The aim of this study was to compare the data of patients who underwent gastric cancer surgery as laparoscopically completedand converted to open surgery and draw attention to complications arising from trocar entry.Materials and Methods: This study included 211 patients who underwent laparoscopic gastric cancer surgery. Patients were dividedin to two groups as laparoscopically completed and converted to open surgery. Demographics parameters and perioperative datawere retrospectively analyzed.Results: The median age of the study group was 62 (19-91) years and 68.2% were males. Conversion occured in 16 patients (7.5%).The reasons for conversion were locally advanced tumor (n=6), complications due to trocar insertion (n=4), technical difficultyin performing esophagojejunostomy anastomosis (n=4), leakage in esophagojejunostomy anastomosis (n=1), and persistentbradycardia (n=1). Intraoperative blood loss was higher and time to oral intake was longer in the conversion group. No significantdifference was found in terms of demographic parameters, operative time, length of hospital stays, the rate of postoperativecomplications, reoperation, 30-day mortality.Conclusion: Complications due to trocar entry is an unpredictable and preventable conversion reason in laparoscopic gastric cancersurgery. Thin patients are riskier for complications during abdominal access. Abdominal access should be performed with an opentechnique in thin patients